Examining the Influence of ICT on the Teaching and Learning of Mathematics in Colleges of Education in Ghana: An Empirical Review - Kissi, Dora; Akyea, Seth Ntow; Ayete, Emmanuel Larbi; Kwarteng , Daniel (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study examined the influence of information and communication technology (ICT) on the pedagogy and acquisition of mathematical knowledge in colleges of education in Ghana. The analysis of how information and communication technology (ICT) is employed in the instruction and acquisition of mathematical concepts is conducted through the utilisation of the Technological Pedagogical Content Knowledge (TPACK) framework. The study employed a desktop study methodology. The study emphasises the significance of educators having proficiency in the three domains of Technological Pedagogical Content Knowledge (TPACK) to successfully integrate technology into their teaching practises. The paper additionally examines the strategies implemented by the Ghanaian government to promote the incorporation of information and communication technology (ICT) within educational establishments. The present study suggests that it is imperative to provide fundamental information and communication technology (ICT) resources, such as computers, laptops, and infrastructure, in order to facilitate the successful incorporation of ICT into the educational process within Colleges of Education in Ghana schools.